Hydrological impacts of ethanol-driven sugarcane expansion in Brazil. (15th March 2021) - Duden, A.S.; Verweij, P.A.; Kraak, Y.V.; van Beek, L.P.H.; Wanders, N.; Karssenberg, D.J.; Sutanudjaja, E.H.; van der Hilst, F.
Abstract: Ethanol production in Brazil is projected to double between 2012 and 2030 in order to meet increased global demand, resulting in the expansion of sugarcane cultivation. Sugarcane expansion drives both direct and indirect land-use changes, and subsequent changes in hydrology may exacerbate problems of (local) water scarcity. This study assesses the impacts of projected ethanol-driven sugarcane expansion on agricultural and hydrological drought in Brazil. Drought due to sugarcane expansion is modelled using a spatial terrestrial hydrological model (PCR-GLOBWB) with spatiotemporally variable land-use change and climate change scenarios as input. We compare an ethanol scenario with increased ethanol demand to a reference situation in which ethanol demand does not increase. The results show that, on average, 29% of the Centre West Cerrado region is projected to experience agricultural drought between 2012 and 2030, and the drought deficit in this region is projected to be 7% higher in the ethanol scenario compared to the reference. The differences between the ethanol and the reference scenario are small when averaged over macro-regions, but can be considerable at a local scale. Differences in agricultural and hydrological drought between the ethanol and reference scenario are most notable in the Centre West Cerrado and Southeast regions. Locally, considerable changes may also occur in other regions, including the Northeast Coast and Northern Amazon region. Because the South East and Centre West Cerrado regions are responsible for a large proportion of agricultural production, increased agricultural drought may result in significant economic losses, while increased hydrological drought could exacerbate existing problems of water supply to large metropolitan areas in these regions. The identification of areas at risk of increased droughts can be important information for policy makers to take precautionary measures to avoid negative hydrological impacts of increased ethanol demand. Highlights: Hydrological impacts of increased ethanol demand show strong spatial variation. Ethanol-driven sugarcane expansion may lead to increased problems of water scarcity. Sugarcane expansion is expected to result in more intense agricultural drought by 2030. High ethanol demand results in >50% increase in water use for irrigation in 2030.